A Bibliometric History of the Journal of Psychology Between 1936 and 2015. - Tur-Porcar, Ana; Mas-Tur, Alicia; Merigó, José M.; Roig-Tierno, Norat; Watt, John (Journal of Psychology, 2018)
The Journal of Psychology: Interdisciplinary and Applied is a leading international journal in psychology dating back to 1935. This study examines its publications since its creation utilizing a bibliometric analysis. The primary objective is to provide a complete overview of the key factors affecting the journal. This analysis includes such key issues as the publication and citation structure of the journal, its most cited articles, and the leading authors, institutions, and countries referenced in the journal. The work uses the Scopus database to classify the bibliographic material. Additionally, the analysis provides a graphical mapping of the bibliographic data by using visualization of similarities viewer software. This software uses several bibliometric techniques including co-citation, bibliographic coupling and co-occurrence of keywords. The Journal of Psychology is strongly connected to most of the current leading journals in psychology, and currently has a 5-year impact factor of 1.77 (Thomson Reuters, 2015Journal Citation Reports).